Seroprevalence of COVID-19 antibody among children aged 5-17 years in an urban and rural area of Ernakulam District, Kerala - Saanu Sidharthan; Seenu Shaik; Chitra Tomy; K Sreelakshmi Mohandas; B Poornima; Paediatric COVID19 Seroconversion Group (Wolters Kluwer Medknow Publications, 2022)
Background: The age group of 5-17 years belongs to the vulnerable segment of the population for COVID-19 infection in India. Seroprevalence in this population can therefore allow inferences to be made about the extent of infection. Objectives: The objective of this study was to assess the seroprevalence and to determine the factors associated with COVID-19 antibody among children aged 5-17 years in an urban and rural area of Kochi, Kerala. Methods: A community-based cross-sectional study was undertaken in the urban and rural field practice areas of the community medicine department in a medical college, Kochi. A semi-structured questionnaire was used to collect information about sociodemographic data, history related to COVID-19, and the severe acute respiratory syndrome coronavirus 2 antibody test result. Blood samples were collected and tested for the presence of COVID-19 antibodies using the Wantai test kit after attaining informed assent from the parent/guardian. Results: The seroprevalence of the COVID-19 antibody was 48.3% among participants. The seroprevalence of COVID-19 antibody was higher among children of mothers with skilled/unskilled occupation, residents of rural area, above poverty line category, those with a history of COVID-19, and those who had a history of contact with COVID-19-positive patients. Conclusion: Half of the study population were COVID antibody positive, and the rest were at risk of infection. Therefore, adherence to COVID-19 guidelines is essential to control further spread of infection among children.